A responsabilidade civil em casos de stalking e cyberstalking: um estudo comparado entre os ordenamentos jurídicos do Brasil e do Estados Unidos da América - Carvalho, André Furegate de (2023)
The study's main purpose is to promote an analysis of civil liability related to obsessive stalking, an unlawful act usually known as stalking and/or cyberstalking. To this end, it will require addressing how the legal systems of Brazil and the United States are handling this particular case. After presenting the concepts and definitions of the conduct based on the legal theory, due to the lack of specific civil legislation on the subject in Brazil, the study proceeds to a case-law analysis of the illicit conduct judged by the São Paulo Court of Appeals, and the North American legislation and its application by the main courts. Therefore, the study specific purposes, derived from the primary end, consisted into the analysis of the historical context of the digital revolution, the doctrinal analysis regarding the concept of obsessive stalking, as well as the cases found in the Brazilian courts of justice and the North American legislation. Finally, after the comparison between the two legal systems, it will be presented a legislative proposal on the subject along with the conclusion of the studies. As a research methodology, it was necessary to compile a bibliographical survey with the collection of data and information and, following the identified and analyzed collected material, a comparative study of the theme was carried out